MULTIPLIKASI EMPAT VARIETAS KRISAN MELALUI TEKNIK KULTUR JARINGAN - Zainuddin Basri (Universitas Tadulako, 2008)
The aim of this experiment was to determine a suitable medium composition for multiplication of each chrysan variety tested. This experiment used Split Plot Design. The main plot was chrysant varieties consisted of four varieties, namely Yellow Fuji, White Fuji, Elen van Lengen and Tawn Talk. Subplot was combination of auxin and BAP consisted of three combinations, namely 0.50 ppm NAA + 1.50 ppm BAP; 0.25 ppm IBA + 1.50 ppm BAP and 0.50 ppm IBA + 1.50 ppm BAP. Therefore, there were 12 treatment combinations and each combination used three replications, with the total of 36 experimental units. Results of this experiment indicated for differences of varieties and media composition tested on the multiplication rate of chrysant. Medium composition suitable for multiplication of chrysant varieties Yellow Fuji, Elen van Lengen and Tawn Talk was Murashige and Skoog basal medium supplemented with 0.25 ppm IBA and 1.50 ppm BAP, whilst for variety White Fuji was culture medium added with 0.50 ppm NAA and 1.50 ppm BAP, with the projection of number of plants produced on each variety at such media composition was 20.88; 13.77; 7.84 and 21.39 million plants per year